AUGMENTED REALITY-BASED LEARNING MEDIA DEVELOPMENT - Hendra Nelva Saputra; Salim Salim; Nurul Idhayani; Tri Kukuh Prasetiyo (STAI Hubbulwathan Duri, 2020)
The purpose of this study is to create an augmented reality based learning media. Augmented reality development on media platform is a learning media innovation that is not taking place much in Southeast Sulawesi. Augmented reality has the ability to combine virtual and real objects together so that it can create quality learning and learning. The products developed in this study are markers and augmented reality applications. The marker developed will be placed on the book. While augmented reality applications will be installed on smartphones so it ACTS as a marker reader. This research is a development study using the model Lee Owens. The object of this study is a learning media expert, a material expert, and eight students of Information Technology Education. Data collection is done using likert scale interview techniques and instruments. The results of the test assessments of the learning media experts obtain highly valid 87.20% worth of worthiness. The results of the material expert test assessments get a valid rating of 82.65%. The results of small group test assessments get an average of valid 80,89%. The assessment of the study media expert, the materials expert, and the small group test indicates that a augmented reality based media is so valid and valid that it can be used in the learning process after doing a small revision.